2004
DOI: 10.1080/13548500410001670771
|View full text |Cite
|
Sign up to set email alerts
|

Students' personality and ratings of clinical competence in medical school clerkships: a longitudinal study

Abstract: This study was designed to examine the associations between students' personality and assessments of their clinical competence in medical school. A set of questionnaires was completed by 1710 medical students to measure their self-esteem, sociability, loneliness, general anxiety, test anxiety, neuroticism (emotionality), perceptions of early relationships with parents, and general health. Students were divided into three groups of the low, moderate, and high competent based on the number of 'Honours' ratings t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
0
16
1
2
Order By: Relevance
“…appraisal of stressful life events, general anxiety and test anxiety, external locus of control, intensity and chronicity of loneliness experiences, extraversion, self-esteem, perceptions of early relationships with parents and peers and measures of over-or underconfidence) could significantly predict performance on medical licensing examinations (Hojat et al 1988). Also, we found that higher scores on measures of self-esteem and extraversion, lower scores on loneliness, and perceptions of satisfactory relationship with parents in childhood (Hojat et al 2004a) could predict global ratings of clinical competence in core clerkships in medical school. Furthermore, inclusion of a set of the aforementioned personality measures to the prediction model could substantially increase (from 0.32 to 0.56) the magnitude of correlations between academic attainment predictors already in the statistical model ( previous academic grades and scores of the Medical College Admission Test, the MCAT) and the criterion measure (scores on Part 1 of the examinations of the National Board of Medical Examiners) (Hojat et al 1988).…”
Section: Personality In the Context Of Medical Education And Patient mentioning
confidence: 55%
See 2 more Smart Citations
“…appraisal of stressful life events, general anxiety and test anxiety, external locus of control, intensity and chronicity of loneliness experiences, extraversion, self-esteem, perceptions of early relationships with parents and peers and measures of over-or underconfidence) could significantly predict performance on medical licensing examinations (Hojat et al 1988). Also, we found that higher scores on measures of self-esteem and extraversion, lower scores on loneliness, and perceptions of satisfactory relationship with parents in childhood (Hojat et al 2004a) could predict global ratings of clinical competence in core clerkships in medical school. Furthermore, inclusion of a set of the aforementioned personality measures to the prediction model could substantially increase (from 0.32 to 0.56) the magnitude of correlations between academic attainment predictors already in the statistical model ( previous academic grades and scores of the Medical College Admission Test, the MCAT) and the criterion measure (scores on Part 1 of the examinations of the National Board of Medical Examiners) (Hojat et al 1988).…”
Section: Personality In the Context Of Medical Education And Patient mentioning
confidence: 55%
“…In a study with students at Jefferson Medical College (Fenderson et al 1999), it was found that students in the top 20% of the class who declined an invitation to participate in an honors program in pathology scored higher on the Neuroticism scale of the EPQ. In another study, we found that medical students who received lower marks on clinical competence were more likely to score lower on the Extraversion scale of the EPQ (Hojat et al 2004a). It was also found that those who were in the top half of their class in clinical competence evaluations scored significantly lower on the Neuroticism scale of the EPQ (Hojat et al 1996a).…”
Section: (6) the Eysenck Personality Inventorymentioning
confidence: 81%
See 1 more Smart Citation
“…Multiple estimates of personality were employed by Hojat et al. 33 Their study was conducted with 1710 students attending Jefferson Medical College in Philadelphia, USA over nine intake years. They used abridged versions of six personality measures; the rationales and associated psychometrics for the use of these abridged versions in medical students and other health profession students had been reported previously 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Comprehensive reviews have recognised personality as an influencing factor on many aspects of medical students' successful and healthy progression through medical training [7,8] . The literature is clear that certain personality traits can influence or predict various aspects of academic performance, [9][10][11][12][13] including subsequent performance in postgraduate training, [14] subclinical competence, [15,16] expression of empathy, [17,18] subjective well-being, [19,20] mental toughness, [21] attitudes to work, burnout and stress, [5] and career interests [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%